2017
DOI: 10.1186/s13019-017-0569-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there a correlation between late re-exploration after cardiac surgery and removal of epicardial pacemaker wires?

Abstract: BackgroundRe-exploration for bleeding accounts for increased morbidity and mortality after major cardiac operations. The use of temporary epicardial pacemaker wires is a common procedure at many departments. The removal of these wires postoperatively can potentially lead to a serious bleeding necessitating intervention.MethodsFrom Jan 2011 till Dec 2015 a total of 4244 major cardiac procedures were carried out at our department. We used temporary epicardial pacemaker wires in all cases. We collected all re-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
3
6
0
3
Order By: Relevance
“…While the use of antiplatelet agents and anticoagulation is hypothesized to play a role in this complication, larger numbers would be needed to develop definitive results. Despite these limitations, our findings are in keeping with prior studies that report a very low risk of tamponade following TEPW removal 2,3 …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…While the use of antiplatelet agents and anticoagulation is hypothesized to play a role in this complication, larger numbers would be needed to develop definitive results. Despite these limitations, our findings are in keeping with prior studies that report a very low risk of tamponade following TEPW removal 2,3 …”
Section: Discussionsupporting
confidence: 89%
“…This is a contemporary study examining the rates of bleeding and tamponade following TEPW removal at a single institution. Our center's rate of 9.4 cases per 10 000 is very similar to the Cleveland Clinic experience of 9.7/10 000, 2 and half of that experienced by Bougioukas et al 3 (18/10 000).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Sites of insertion of temporary pace-maker wires and of chest tubes may account for less frequent causes of excessive bleeding. 5,10,28 These findings suggest that most of severe bleeding events can be prevented by a meticulous surgical technique and systematic checking of potential sites of bleeding. After having observed that severe bleeding originated mostly from surgical sites, 16 Loor et al 7 introduced a checklist for a systematic intraoperative evaluation of potential surgical sources of bleeding.…”
Section: Discussionmentioning
confidence: 88%